Old State House at 206 Washington Street, November, 1981 - Cann, Donald (Tufts Archival Research Center, 2005)
Street-level view east-northeast of the southeast corner of the Old State House, located at 206 Washington Street. Buildings lining the north side of State Street are included in the background of the photograph. Street lights and traffic signs and signals also line State Street. A delivery truck and van are parked along the west side of Devonshire Street. 4 15/16 x 3 1/2 Photographs